Aplikasi Logika Fuzzy Pada Pengelompokan Nilai SWR Ideal Antena dengan Bahan Dasar Allumunium - roni kartika pramuyanti (Retii, 2020)
The SWR is a comparison of the resistance value, here the SWR value is classified. Assisted by the FIS editor of the Matlab program, several classification results will be obtained. With the Fuzzification process, 3 types of classifications will be obtained, namely less than ideal, ideal and not ideal. There are 2 ways to calculate the SWR which all produce ideal results that are almost the same as the results of the observations. The use of the FIS editor in the classification here is in the form of traces, each of which has a range of values, although each input / input only has one value, so the FIS editor uses the triangle membership function. It can be concluded that the SWR value that can make an instrument operate properly is not necessarily ideal because instruments such as antennas will be heavily influenced by external environmental factors.